2020
DOI: 10.4103/ijstd.ijstd_143_15
|View full text |Cite
|
Sign up to set email alerts
|

What are the most common sexually transmitted bacteria in women with cervico-vaginitis nowadays?

Abstract: Introduction: Cervico-vaginitis is usually the initial infection which, when undiagnosed, can evolve to salpingitis with tubal infertility, ectopic pregnancy, and chronic pelvic pain as consequences. This study aimed at identifying the sociodemographic profile and clinical presentation of women diagnosed with cervico-vaginitis, as well as the microorganisms isolated. Materials and Methods: This cross-sectional, descriptive study was carried out between October 1, 2013, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Isolation of M. hominis and U. parvum was significantly associated with bacterial vaginosis ( P = 0.04 and 0.003, respectively). In contrast, Nkwabong[ 13 ] in their study found among all women, genital tract mycoplasmas were the most encountered microorganisms (67.9%). This might reflect changing trends in causative organisms.…”
Section: Discussionmentioning
confidence: 79%
“…Isolation of M. hominis and U. parvum was significantly associated with bacterial vaginosis ( P = 0.04 and 0.003, respectively). In contrast, Nkwabong[ 13 ] in their study found among all women, genital tract mycoplasmas were the most encountered microorganisms (67.9%). This might reflect changing trends in causative organisms.…”
Section: Discussionmentioning
confidence: 79%